When a metastatic breast cancer is mimicking a pancreatic cancer: case report and review of the literature. Issue 4 (3rd July 2020) - Derouane, Françoise; Yombi, Jean-Cyr; Baurain, Jean-François; Danse, Etienne; Komuta, Mina; Yildiz, Halil
ABSTRACT: We report the case of a 51 year-old female who complained of jaundice and weight loss. At the time of presentation, she had been in remission from a stage 2a ductal breast carcinoma for 58 months. The clinical presentation was suggestive of a primary pancreas cancer with liver metastases and retroperitoneal lymph nodes. We performed liver and pancreas biopsies that demonstrate a relapse of her old breast carcinoma with positive hormone receptors and HER2 positive. Conservative treatment by chemotherapy was given with Paclitaxel – Trastuzumab and Pertuzumab. Pancreatic metastases are uncommon. Furthermore, pancreatic metastases from breast cancer are very rare. We performed a review of the literature and found 48 cases of pancreatic metastases from breast cancer. We would like to highlight by this case that when a pancreatic lesion appears, in patients with a past history of cancer, physicians must not forget the possibility of metastases from primary tumor even if the initial stage, of the tumor, is low. However the diagnosis is not always easy. If liver and pancreatic lesions occur simultaneously, the clinical presentation can mimic metastatic primary pancreatic cancer. Therefore performing biopsy is highly recommended for making the correct diagnosis and also for the staging of the disease and the choice of the best treatment according to immunohistochemical analysis.